2015
DOI: 10.14814/phy2.12357
|View full text |Cite
|
Sign up to set email alerts
|

Charting the course of renal cryoinjury

Abstract: We sought to characterize a minor renal cryoinjury that allows investigation into renal damage processes and subsequent endogenous repair mechanisms. To achieve this, we induced a small cryoinjury to mice, in which the transient superficial application of a liquid nitrogen-cooled cryoprobe to the exposed kidney induces a localized lesion that did not impair renal function. The resulting cryoinjury was examined by immunohistochemistry and Laser-Doppler flowmetry. Within hours of cryoinjury induction, tubular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Rodriguez-Porcel et al demonstrated impaired kidney response to vasodilators (acetylcholine and sodium nitroprusside), but they used electron-beam computed tomography, which is difficult to implement routinely. 20 LDF has been extensively used to assess renal microcirculation in mice in ischemiareperfusion, 21,22 preconditioning, 23 renal cryoinjury 24 or other models. 25 LASCA and LDF both use laser speckle patterns, but the analysis techniques differ.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Porcel et al demonstrated impaired kidney response to vasodilators (acetylcholine and sodium nitroprusside), but they used electron-beam computed tomography, which is difficult to implement routinely. 20 LDF has been extensively used to assess renal microcirculation in mice in ischemiareperfusion, 21,22 preconditioning, 23 renal cryoinjury 24 or other models. 25 LASCA and LDF both use laser speckle patterns, but the analysis techniques differ.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, this boasted release of Ccl2 explains for the significant infiltration of macrophages during the early inflammation phase in Ifnar del mice. Under normal conditions, however, this process of activation and recruitment takes three days [ 39 ]. In the current study, we observed that WT mice showed a regular infiltration of regeneration supporting macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian models of acute kidney injury (AKI) have been performed in murine models (Shoskes et al, 1990;Wei and Dong, 2012) and have included surgical approaches to induce ischemia/reperfusion injuries (Duffield et al, 2006) and injection of nephrotoxins such as Cisplatin (Ramesh and Reeves, 2003). In addition, a more recent publication describes a renal cryo-injury model aimed at uncovering endogenous damage and repair processes (Abdulmahdi et al, 2015).…”
Section: The Regenerative Capacity Of the Mammalian Kidneymentioning
confidence: 99%